Valorisation of CO2 into Value-Added Products via Microbial Electrosynthesis (MES) and Electro-Fermentation Technology - Marzuqa Quraishi; Kayinath Wani; Soumya Pandit; Piyush Kumar Gupta; Ashutosh Kumar Rai; Dibyajit Lahiri; Dipak A. Jadhav; Rina Rani Ray; Sokhee P. Jung; Vijay Kumar Thakur; Ram Prasad (Fermentation, 2021)
Microbial electrocatalysis reckons on microbes as catalysts for reactions occurring at electrodes. Microbial fuel cells and microbial electrolysis cells are well-known in this context; both prefer the oxidation of organic and inorganic matter for producing electricity. Notably, the synthesis of high energy-density chemicals (fuels) or their precursors by microorganisms using bio-cathode to yield electrical energy is called Microbial Electrosynthesis (MES), giving an exceptionally appealing novel way for producing beneficial products from electricity and wastewater. This review accentuates the concept, importance and opportunities of MES, as an emerging discipline at the nexus of microbiology and electrochemistry. Production of organic compounds from MES is considered as an effective technique for the generation of various beneficial reduced end-products (like acetate and butyrate) as well as in reducing the load of CO2 from the atmosphere to mitigate the harmful effect of greenhouse gases in global warming. Although MES is still an emerging technology, this method is not thoroughly known. The authors have focused on MES, as it is the next transformative, viable alternative technology to decrease the repercussions of surplus carbon dioxide in the environment along with conserving energy.